Occurrence and Genotypic Characterization of Selected Multidrug-resistant ESKAPE-E Pathogens Isolated from Integrated Smallholder Fresh Produce Farms - Sheldon Viviers; Loandi Richter-Mouton; Jonathan Featherston; Lise Korsten (Journal of Food Protection)
Antimicrobial resistance (AMR) ranks among the top ten global public health threats, with extended-spectrum β-lactamase (ESBL)-producing Enterobacterales and Pseudomonas aeruginosa emerging as multidrug-resistant (MDR) priority pathogens. This study aimed to evaluate the presence and characteristics (phenotypic and genotypic AMR profiles) of ESBL/AmpC-producing Enterobacterales and P. aeruginosa isolates obtained from the water-soil-plant nexus on smallholder fresh produce farms in South Africa. Samples of irrigation water (n = 44), soil (n = 85), and fresh produce (n = 95) were collected from six smallholder farms. Potential MDR bacteria were isolated using selective enrichment, chromogenic media, and identified with MALDI-TOF MS. Antimicrobial resistance was assessed via double-disk diffusion against 13 different antibiotic classes, while 20 selected isolates were genotypically characterized using whole-genome sequencing (WGS) (Illumina MiSeq). ESBL/AmpC-producing isolates were detected in 17% of samples (38/224), primarily from fresh produce (54%), followed by soil (31%) and water (15%). The dominant Enterobacterales species identified from all three matrices included Enterobacter spp. (26%), Klebsiella spp. (26%), Serratia spp. (17%), and Escherichia coli (9%). Phenotypically, 47% and 43% of the isolates were classified as ESBL and AmpC-producers, respectively, with resistance to beta-lactams, aminoglycosides, and glycylcyclines. Notably, WGS analysis indicated the presence of clinically significant AMR and virulence genes among isolates from the environment, particularly those associated with mobile genetic elements. The results from the study add to the limited national and international knowledge of AMR prevalence in the smallholder agricultural landscape, needed for the introduction of appropriate intervention strategies and future risk assessment of the informal supply chain.